Intermittent Hypoxia Causes Insulin Resistance in Lean Mice Independent of Autonomic Activity - Iiyori, Nao (American Thoracic Society, 2007)
Rationale and Objectives: Although many clinical physiology and epidemiology studies show an association between obstructive sleep apnea (OSA) and markers of insulin resistance, no causal pathway has been established. The purpose of the current study was to determine if the intermittent hypoxia (IH) stimulus that characterizes OSA causes insulin resistance in the absence of obesity. Furthermore, we assessed the impact of IH on specific metabolic function in liver and muscle. Finally, we examined the potential mechanistic role of the autonomic nervous system (ANS) in mediating insulin resistance in response to IH. Methods and Results: Hyperinsulinemic euglycemic clamps were conducted and whole-body insulin sensitivity, hepatic glucose output, and muscle-specific glucose utilization assessed in conscious, chronically instrumented adult male C57BL/6J mice exposed to (1) IH (achieving a nadir of Fi(O(2)) = 5–6% at 60 cycles/h for 9 h), (2) intermittent air as a control, (3) IH with ANS blockade (hexamethonium), or (4) IA with ANS blockade. IH decreased whole-body insulin sensitivity compared with intermittent air (38.8 ± 2.7 vs. 49.4 ± 1.5 mg/kg/min, p < 0.005) and reduced glucose utilization in oxidative muscle fibers, but did not cause a change in hepatic glucose output. Furthermore, the reduction in whole-body insulin sensitivity during IH was not restored by ANS blockade. Conclusion: We conclude that IH can cause acute insulin resistance in otherwise lean, healthy animals, and that the response is associated with decreased glucose utilization of oxidative muscle fibers, but that it occurs independently of activation of the ANS.